2016
DOI: 10.1080/10599231.2016.1166024
|View full text |Cite
|
Sign up to set email alerts
|

Investor Sentiment and Stock Market Volatility: Evidence from India

Abstract: In this article, the authors probe the role of irrational investor sentiment in the determination of Indian stock market volatility. The authors developed a new irrational aggregate sentiment index (IASI) to examine the issue. The conditional volatility is extracted from the nonlinear univariate models for the market indices and the IASI. The vector autoregression (VAR) is carried out to analyze the relationship between the volatility of irrational aggregate sentiment index and stock market volatility. The aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 79 publications
1
22
0
Order By: Relevance
“…Rahman and Shamsuddin (2019) studied the excess price ratio and its influence on investor sentiment and found that the price to earnings ratio increased with a rise in investors' sentiment. Kumari and Mahakud (2016) and Chandra and Thenmozhi (2013) studied the impact of investor sentiment in the Indian capital market. They found a positive relationship between investor sentiment and market volatility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rahman and Shamsuddin (2019) studied the excess price ratio and its influence on investor sentiment and found that the price to earnings ratio increased with a rise in investors' sentiment. Kumari and Mahakud (2016) and Chandra and Thenmozhi (2013) studied the impact of investor sentiment in the Indian capital market. They found a positive relationship between investor sentiment and market volatility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This was a period characterised by very high sentiment due to the positive outlook on financial markets. Naik and Padhi (2016) and Kumari and Mahakud (2016) found that sentiment influences the conditional volatility on the Indian market. The latter study also found that the relationship between stock return volatility and sentiment was persistent, suggesting that investor sentiment in India does play a significant role in determining the stock market volatility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The aggregate sentiments involve herding behaviour, which refers to an attitude that tend to believe more on others' information rather than that on one's own information (De long et al, 1990) and going against the herd by informed arbitrageurs is costly and risky as well (Shleifer & Vishny, 1997). Again, Kumari and Mahakud (2016) have found a unidirectional causality from sentiment to the stock market volatility. Tuyon, Ahmad, and Matahir (2016) also have revealed that investor sentiment has significant effects on the short run and long run stock market returns in the Malaysian stock market and the effects are heterogeneous across firm sizes, industry groups and market states etc.…”
Section: Literature Reviewmentioning
confidence: 99%